2021
DOI: 10.5194/wes-6-1015-2021
|View full text |Cite
|
Sign up to set email alerts
|

WRF-simulated low-level jets over Iowa: characterization and sensitivity studies

Abstract: Abstract. Output from 6 months of high-resolution simulations with the Weather Research and Forecasting (WRF) model are analyzed to characterize local low-level jets (LLJs) over Iowa for winter and spring in the contemporary climate. Low-level jets affect rotor plane aerodynamic loading, turbine structural loading and turbine performance, and thus accurate characterization and identification are pertinent. Analyses using a detection algorithm wherein the wind speed above and below the jet maximum must be below… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…The lidar measurements used in this study were performed on eight height levels, most levels separated by a distance of 50 m. As LLJ cores can be of varying vertical extent, it is likely that this vertical resolution might not capture all LLJs. We refer to Nunalee and Basu (2014) and Aird et al (2021) for discussion on the sensitivity of detecting LLJs to the height resolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lidar measurements used in this study were performed on eight height levels, most levels separated by a distance of 50 m. As LLJ cores can be of varying vertical extent, it is likely that this vertical resolution might not capture all LLJs. We refer to Nunalee and Basu (2014) and Aird et al (2021) for discussion on the sensitivity of detecting LLJs to the height resolution.…”
Section: Discussionmentioning
confidence: 99%
“…As the definitions of LLJs vary in the literature, we follow the most recent recommendation by Aird et al (2021), applying both a fixed and a relative criterion for LLJ classification. A profile was classified as a strong LLJ if there was a well-pronounced local maximum in the wind profile where the core speed was both at least 20% and at least 2 m s −1 stronger than the weakest wind speed in the lidar profile both above and below the jet core.…”
Section: Wind Profile Classificationmentioning
confidence: 99%
“…LLJ frequency and characteristics are sensitive to the definition employed [50,51]. Use of only an absolute wind speed threshold for detection (i.e., maximum wind speed at the jet core exceeds that above and below the jet by X ms −1 ) results in higher speed LLJs, whereas the use of only a relative (or variable) wind speed threshold (i.e., jet core wind speed exceeds wind speeds above and below by X%) results in lower speed LLJs [52].…”
Section: Llj Detectionmentioning
confidence: 99%
“…PBLH is analyzed hourly and is as defined within the MYNN scheme as the lowest height at which modeled turbulent kinetic energy (TKE) < 1.0 × 10 −6 m 2 s −2 [51].…”
Section: Analysis Of Meteorological Conditions Associated With Lljsmentioning
confidence: 99%
“…All lidar wind profiles were classified into one of the following six classes: idealized, negative, LLM, transition, weak LLJ or strong LLJ. As the definitions of LLJs vary in the literature, we follow the most recent recommendation by Aird et al (2021), applying both a fixed and a relative criterion for LLJ classification. Using hourly model data of wind profiles up to approximately 530 m height over Iowa (USA) during a period of 6 months (December 2007 to May 2008), Aird et al (2021) concluded that defining LLJs based on only a fixed criterion compared to only using a relative criterion identified different LLJs 40 % of the time.…”
Section: Wind Profile Classificationmentioning
confidence: 99%